Projections of food consumption and the health impacts associated with changes in dietary and weight-related risk factors - Springmann, M; Mason-D'Croz, D; Robinson, S; Wiebe, K; Scarborough, P (2016)
Dietary and weight-related risk factors currently account for a greater burden of disease than any other group of risk factors. Here we estimate the changes in the health burden that is due to changes in selected dietary and weight-related risk factors for the year 2035 for 155 world regions. For our analysis, we linked the IMPACT agriculture-economic model, which we used to project future food consumption, to a comparative risk assessment of changes in fruit and vegetable consumption, red meat consumption, bodyweight among adults, and moderate and severe stunting among children. We find that changes in dietary and weight-related risk factors between 2015 and 2035 could lead to 76 million DALYs saved, corresponding to 1.7 million avoided deaths globally. About half of the DALYs are projected to be saved in South East Asia, 25% in the Western Pacific, 20% in Africa, and 2% in high-income countries, among others. Most DALYs were saved due to increased fruit and vegetable consumption (67 million), followed by reductions in underweight (31 million) and stunting (19 million), but they were partly offset by additional DALYs due to increased prevalence of obesity (27 million) and overweight (3 million), and increased red meat consumption (12 million).